First detection of the growing humps at the rapidly rising stage of dwarf novae AL Com and WZ Sge - Ishioka, R.; Uemura, M.; Matsumoto, K.; Ohashi, H.; Kato, T.; Masi, G.; Novak, R.; Pietz, J.; Martin, B.; Starkey, D.; Kiyota, S.; Oksanen, A.; et al. (2002)
We report on time-series photometric observations in the earliest stages of superoutbursts of the extreme dwarf novae, AL Com and WZ Sge, which started on 2001 May after the 6 years quiescence and on 2001 July after the 23 years quiescence, respectively. We detected the growth of ``early superhumps'' during the each rising stage. Our observations reject the mass transfer instability for the trigger of the superoutburst of WZ Sge stars, and show the existence of some relations between the ``early superhumps'' and the spiral structure, which gives a hint of the origin of the ``early superhumps.''
Keywords: Astrophysics; STARS: CATACLYSMIC VARIABLES; STARS: DWARF NOVAE; STARS: INDIVIDUAL (WZ SGE)